f(n)=3f(n-1)-1

Simple and best practice solution for f(n)=3f(n-1)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(n)=3f(n-1)-1 equation:


Simplifying
f(n) = 3f(n + -1) + -1

Multiply f * n
fn = 3f(n + -1) + -1

Reorder the terms:
fn = 3f(-1 + n) + -1
fn = (-1 * 3f + n * 3f) + -1
fn = (-3f + 3fn) + -1

Reorder the terms:
fn = -1 + -3f + 3fn

Solving
fn = -1 + -3f + 3fn

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '3f' to each side of the equation.
3f + fn = -1 + -3f + 3f + 3fn

Combine like terms: -3f + 3f = 0
3f + fn = -1 + 0 + 3fn
3f + fn = -1 + 3fn

Add '-3fn' to each side of the equation.
3f + fn + -3fn = -1 + 3fn + -3fn

Combine like terms: fn + -3fn = -2fn
3f + -2fn = -1 + 3fn + -3fn

Combine like terms: 3fn + -3fn = 0
3f + -2fn = -1 + 0
3f + -2fn = -1

Reorder the terms:
1 + 3f + -2fn = -1 + 1

Combine like terms: -1 + 1 = 0
1 + 3f + -2fn = 0

The solution to this equation could not be determined.

See similar equations:

| (((1300000-x)/2)/1300000)=0.1 | | 15=23-4m | | 14x+11=4x+11 | | h(-3)=3x-3 | | =11+0.9(y-10) | | 25+x=78 | | 2x+7=3x-(6x-2) | | 2(p+5)-3p=14 | | X+X+1(X+2)=160 | | 4x+-3x+-5x= | | -5y+3-4y=2 | | 2.14-0.3x=2.24 | | 1/2=x1/4 | | 75000=x(x+3) | | 5(x+4)=3[x-(4-x)] | | 15x+30=15x-90 | | -2.9=f+4.3 | | 2x-12y+5=0 | | sinx+14.87cosx=1.5 | | 0.5x+0.08=0.13 | | 3(g-2)+2=5g-7-2g | | 12x-(3x-9)=27 | | (x-2)(x-2)(x+3i)(x-3i)=0 | | 175000=x(x+3) | | 7x+10000=5x+14000 | | 7x+10000=10x+6000 | | f(-4)=8 | | (-5(x=6)/3)=10 | | 8750=x(x+3) | | 2n+3.75=7n | | 2s-13=27 | | 3(2p+5)-4(p+3)= |

Equations solver categories